Evaluation of Allelopathic Potential and Phytochemical Screening of Some Medicinal Plant Species of Nepal - Devkota, Anjana (International Journal of Pharmaceutical & Biological Archive, 2013)
Evaluation of Allelopathic Potential and Phytochemical Screening of Some Medicinal Plant Species of Nepal